Global Propagation of Ionospheric Disturbances Associated With the 2022 Tonga Volcanic Eruption. Issue 7 (5th April 2022) - Themens, David R.; Watson, Chris; Žagar, Nedjeljka; Vasylkevych, Sergiy; Elvidge, Sean; McCaffrey, Anthony; Prikryl, Paul; Reid, Ben; Wood, Alan; Jayachandran, P. T.
Abstract: In this study, we use measurements from over 4, 735 globally distributed Global Navigation Satellite System receivers to track the progression of traveling ionospheric disturbances (TIDs) associated with the 15 January 2022 Hunga Tonga‐Hunga Ha'apai submarine volcanic eruption. We identify two distinct Large Scale traveling ionospheric disturbances (LSTIDs) and several subsequent Medium Scale traveling ionospheric disturbances (MSTIDs) that propagate radially outward from the eruption site. Within 3, 000 km of epicenter, LSTIDs of >1, 600 km wavelengths are initially observed propagating at speeds of ∼950 and ∼555 ms −1, before substantial slowing to ∼600 and ∼390 ms −1, respectively. MSTIDs with speeds of 200–400 ms −1 are observed for 6 hrs following eruption, the first of which comprises the dominant global ionospheric response and coincides with the atmospheric surface pressure disturbance associated with the eruption. These are the first results demonstrating the global impact of the Tonga eruption on the ionospheric state. Plain Language Summary: The 2022 Tonga oceanic volcanic eruption and resulting tsunami was an incredibly impulsive and high energy event. Such events can generate strong pressure waves in the atmosphere that can propagate up into the Earth's ionosphere and modulate the plasma therein. Using every available Global Navigation Satellite System (GNSS) receiver from a global network of over 4, 735 instruments, we were able to track the propagation of these waves from the Tonga eruption site around the planet. We show that an initial shock front at speeds of up to 950 ms −1 strongly perturbs the ionospheric electron density near the eruption site and within a narrow extended region to the North, while smaller, slower waves originating from the eruption make up the strongest ionospheric response at distances far away from the eruption region. Small scale ionospheric waves continue to be produced near the eruption for up to 6 hrs after the eruption began. These waves were tracked from the eruption to over 20, 000 km from the epicenter and could very well have persisted beyond the 1 day studied here. Key Points: Highly directional Large Scale traveling ionospheric disturbances (LSTIDs) are generated from the Tonga Eruption at initial speeds up to 950 m/s and propagate potentially as far as 20, 000 km Outside the local area of the eruption, Medium Scale traveling ionospheric disturbances (MSTIDs) coincident with the surface pressure wave form the dominant ionospheric response Secondary MSTIDs continue to be produced in the vicinity of the eruption for up to 6 hr following the event